A Study of Volatility of Capital Flows in India: Exploring the Impact of Reforms and Foreign Investment on India's Capital Flows (Journal of Advances and Scholarly Researches in Allied Education, 2018)
India's capital inflow trend and patterns are aligned with the general developments in other emerging markets. From 1992 to 1998 after the reforms the inflows of capital into the country spurred. The amount of capital inflows was however smaller for India as India remained less open to capital inflows in comparison with many other countries and retained capital outflow controls. The capital inflow trend is showing a clear break from the previous decades, with a significant growth in the mid-1990s, which reveals credible economic reforms and fosters foreign investor confidence, enhances the country's macroeconomic performance and attracts foreign capital. In the post-reform era, capital inflows moved mainly from public inflows to private ones and from debt inflows to non-debt capital inflows. FDI Inflows accelerated and peaked in 1995, but subsequently declined, tilting the compounding of capital inflows into portfolio inflows because FDI procedures were complicated and discretionary, and investment by FII via the financial market route was significantly simplified in India. Changes in a country or currency's economic condition lead to significant capital shifts, often occurring quickly if financial capital is involved. Their potential nature of asset prices over-heating, loss in export competitiveness, and vulnerability to a financial crisis create significant challenges for policy makers. Capital inflows are positively linked to the recipient countries' exchange rate appreciation. The exchange rate typically is greatly affected by equity investment flows, international lending, foreign aid, and foreign remittances flows, while foreign direct investment capital inflows do not significantly affect the exchange rate.